(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Introduction: Psoriatic arthritis (PsA) is established as a multifactorial disease resulting from a complex interplay between genetic, environmental and immunological factors. It is a seronegative arthritis but rheumatoid factor may be present in up to 15% of PsA patients Antibodies recognizing a cyclic citrullinated peptide are highly speciûc for rheumatoid arthritis (RA) but their role in PsA remains unclear. An increased prevalence of anti-CCP antibody in PsA is also reported. Study shows that HLA-DRB1 shared epitope is signiûcantly associated with the presence of anti-CCP antibody in PsA patients but this type of association is not found with other human leukocyte antigens. Objectives: The aim of this study was to investigate the frequency of anti-CCP and RF in PsA patients and their associations with HLA-B locus antigens. Methods: In this cross sectional study, we selected 50 unrelated consecutive patients with PsA according to CASPAR criteria for PsA. 6 ml of blood was collected from each patient for HLAB locus typing, RA test and test for anti-CCP. Patient’s serum samples were tested for RF by Nephelometric system and tests for anti-CCP were done by ELISA. HLA-B locus typing was done by PCR with sequence specific primer. Results: Among 50 PsA patients, 27 (54%) are female and 23 (46%) are male. RA test is positive in 10 (20%) patients and anti-CCP is positive in 7 (14%) patients. Significant association was found between HLA-B*37 and RF (p value= < 0.001). Conclusion: RF is present in 10 (20%) and anti-CCP is present in 7 (14%) PsA patients. HLAB* 37 was significantly found in RF positive patients. J Shaheed Suhrawardy Med Coll 2020; 12(2): 109-114